Social Radio – A Music-Based Approach to Emotional Awareness Mediation - Röcker, Carsten; Etter, Richard (Proceedings of the International Conferences on Intelligent User Interfaces (IUI’07))
This paper presents a novel approach for mediating awareness in small intimate groups. Instead of traditional communication media, music is used to inform users about the presence and mood of multiple remote peers. Based on this conceptual idea, an awareness system called 'Social Radio' was developed. The system consists of several smart artifacts and an underlying multi-user communication infrastructure.
Keywords: Applied computing; Operations research; Human-centered computing; Human computer interaction (HCI)